THE COMMON ECONOMIC SPACE OF RUSSIA, BELARUS, AND KAZAKHSTAN: PRESENT AND FUTURE - Borishpolets, Ksenia; Chernyavsky, Stanislav (CENTRAL ASIA AND THE CAUCASUS, 2012)
On 1 January, 2012, the official opening of the Common Economic Space (CES) of Belarus, Kazakhstan, and Russia, which moved customs control to the outer border of the Customs Union (CU) in July 2011, launched a qualitatively new stage in integration development in the post-Soviet expanse. The objective conditions for consolidating economic cooperation among the three countries have long emerged, the technical work, in the best interests of all the partners concerned, has been carried out, and the top leaders are showing sufficient political will. So there is every reason to believe that the driving force behind post-Soviet integration in the CU-CES format has sprung into action.Flat duty and tax rates on imported goods, sanitary and veterinary control, and technical regulation principles have been in effect for Russia, Belarus, and Kazakhstan alike since the middle of 2011. On 1 January, 2012, a basic set of documents on the CES consisting of 17 agreements came into force that address the rights of migrant workers and the members of their families, standard principles of currency policy, access to railroad transport services, standard regulations for the support of agricultural goods producers, and conditions for ensuring free movement of capital. All of this will help to form a common market with more than 170 million consumers and a total gross product of more than $1,385 billion.Systemic organization of the flows of such large-scale economic resources is already generating real benefits; despite the list of goods to which export limits still apply, goods turnover among the participants of the Customs Union has almost doubled. According to experts, by 2015 integration will afford the participants in the Customs Union an additional 15% increase in GDP amounting to approximately $400 billion.However, in addition to the surface indices, it is expedient to look deeper and appreciate the other innovation benefits owing to the free movement of goods within the framework of mutual trade among Russia, Belarus, and Kazakhstan, the decrease in financial load on commercial enterprises, the removal of administration barriers, the standardization of customs regulations, and……………..